Effect of Covid-19 on the Lifestyles of Vaccinated and Unvaccinated Elite Athletes: A Cross-Country Analysis - Ashouri, Mahdi; Nehzat Norozi tehrani, Sadaf; Karuppasamy Govindasamy; Zouhal, Hassane (Health Nexus, 2023)
Background: The global COVID-19 pandemic has led to widespread home confinement and quarantine measures. Despite ongoing vaccination efforts, some elite athletes have shown hesitancy about getting vaccinated.Aim: This study sought to analyze the impact of COVID-19 on the lifestyles of vaccinated and unvaccinated elite athletes through a cross-country comparison.Methods: In 2021, an online survey was administered to 581 elite athletes aged 18-35 from different countries across four continents. The survey included socio-individual data, the International Physical Activity Questionnaire (IPAQ), the Rapid Eating Assessment for Participants (REAP-S), and the Petersburg Sleep Quality Questionnaire (PSQI). The participants voluntarily agreed to take part in the survey. The data analysis employed U-Mann-Whitney Wilcoxon tests, with a significance level of alpha p< 0.05.Results: The findings demonstrated a significant disparity in the physical activity and dietary habits of vaccinated versus unvaccinated elite athletes (p